The Association Between Parents’ Growth Mindset and Children’s Persistence and Academic Skills - Song, Yuchen; Barger, Michael M; Bub, Kristen L. (Frontiers in Education, 2022)
Parents’ educational beliefs are thought to guide children’s early development in school. The present study explored the association between parent’s growth mindset and elementary school-aged children’s self-reported persistence, as well as teacher-reported reading and math skills in 102 dyads. Findings showed that children self-reported greater persistence when their parents held more growth mindset. Teachers also rated students as more capable readers when their parents endorse a growth, rather than fixed, mindset. Additional analysis indicated that although the effect of parents’ growth mindset on children’s reading skills became non-significant once SES was controlled, the positive association between parents’ mindset and children’s persistence was unaffected by SES. Our study provides evidence that parents can foster motivational tendencies in their children at an early age, even when children may not be able to develop a coherent system of motivational beliefs of their own.